Silica aerogel particle / polyester fiber composite floe and method of making same
Patent Information
- Application Number
- CN202611470061.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
文献4(A newtechnique to prepare a hydrophobic and thermal insulating polyester wovenfabric using electro-spraying of nano-porous silica powder[J].Surface andCoatings Technology, 2019, 366:97-105.)中采用电喷雾方法将二氧化硅气凝胶/氟碳化合物混合物涂覆于聚酯机织物表面,虽然材料的传热率明显降低且耐磨试验后的质量损失低于5%,但其透气性随气凝胶施加量增加而持续下降
[0025](1)本发明通过有机溶剂对聚酯纤维絮片进行溶剂活化处理,调控聚酯纤维表层界面状态,使得二氧化硅气凝胶颗粒以离散状态均匀的附着在单根聚酯纤维表面。
Smart Images

Figure CN122980208A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional textile composite materials technology, and relates to a silica aerogel particle / polyester fiber composite wadding and its preparation method. Background Technology
[0002] Silica aerogel is a nanoporous material characterized by low density, high porosity, and low thermal conductivity, and is hailed as "the lightest solid in the world." Its unique three-dimensional network structure gives it significant advantages in the field of thermal insulation. However, pure aerogel has poor mechanical properties, is brittle and easily broken, which limits its direct use in practical applications.
[0003] To address this issue, silica aerogel is typically composited with fibrous materials. The fibrous materials possess excellent flexibility and processability, which can compensate for the mechanical limitations of aerogel. Through this composite process, the superior thermal insulation properties of aerogel can be combined with the mechanical strength and flexibility of fibers, thereby expanding its application prospects in fields such as thermal insulation textiles and aerospace insulation layers.
[0004] Currently, the main methods for preparing aerogel particle / fiber composites include impregnation, coating, particle filling, bonding, or encapsulation. The basic idea behind these methods is to attach pre-fabricated silica aerogel particles to a fiber substrate using physical or chemical means. However, these conventional methods face three major challenges in practical applications:
[0005] Poor dispersibility of aerogel particles: Due to their small size and high surface energy, silica aerogel particles are prone to agglomeration when directly loaded onto fibrous materials. For example, in Reference 1 (Optically Active Polyurethane / SilicaAerogel Coated Cotton Fabrics for Thermal Protection[J]. Frontiers in Materials, 2021.DOI:10.3389 / fmats.2021.681678.), a coating was prepared by combining photoactive polyurethane and silica aerogel and applied to the surface of cotton fabrics. It was found that in samples with low polyurethane content, aerogel particles mainly existed in the form of aggregates and were unevenly distributed. In addition, patent US9399864B2 also points out that wet slurries made from aerogel particles and fibers can only remain uniform for a short time. During the drying process, particles and fibers may separate, forming stratification along the thickness direction, resulting in excessively high aerogel content and insufficient adhesion between particles in local areas.
[0006] Weak interfacial bonding and easy particle detachment: Simply relying on physical filling or weak interfacial bonding to fix aerogel particles in the fiber structure will cause the particles to detach during use. Reference 2 (Fabrication of silicaaerogel composite blankets from an aqueous silica aerogel slurry. CeramicsInternational, 2018, 44(2):2204-2208.) used silica aerogel slurry containing PVB adhesive to impregnate PE fiber felt, and found that the composite fiber felt had uneven structure and obvious aerogel powder detachment. Patent EP3281928B1 also pointed out that insufficient adhesion between aerogel and fiber felt substrate will cause the two to separate, and this problem is more prominent when the material is made into a flexible thermal insulation material that needs to be bent repeatedly. Patent EP3712111A1 also pointed out that vibration will exacerbate the continuous detachment of aerogel or additives from fiber felt, while using adhesive slurry to reduce dust may increase the thermal conductivity of composite material.
[0007] It is difficult to balance air permeability and thermal insulation performance: While increasing the amount of aerogel particles or adhesives can help improve particle retention, it may also occupy the original air channels between fibers, reducing the air permeability of the material. Reference 3 (Thermophysiological Comfort Analysis of Aerogel Nanoparticle Incorporated Fabric for Fire Fighter's Protective Clothing[J]. Chemical & Materials Engineering, 2014. 2(2):37-43.) found that after applying a silica aerogel particle coating to wool / aramid blended fabrics, a 2% aerogel coating could increase thermal resistance by up to 68.64%, but at the same time reduce air permeability by up to 45.46%; when the aerogel coating content increased to 4%, the air permeability decreased by 61.76%. Reference 4 (A new technique to prepare a hydrophobic and thermal insulating polyester woven fabric using electro-spraying of nano-porous silica powder[J]. Surface and Coatings Technology, 2019, 366:97-105.) describes an electro-spraying method to coat the surface of a polyester woven fabric with a mixture of silica aerogel and fluorocarbon. Although the heat transfer rate of the material is significantly reduced and the mass loss after the abrasion test is less than 5%, its air permeability continues to decrease with the increase of aerogel application.
[0008] In summary, achieving uniform loading and stable bonding of silica aerogel particles on the polyester fiber surface while maintaining the three-dimensional interconnected pores and high air permeability of the polyester fiber flocs is a core technical problem that urgently needs to be solved in the field of aerogel / polyester fiber composite insulation materials. Therefore, the need for a silica aerogel particle / polyester fiber composite flocs and its preparation method to solve the above problems is of great significance. Summary of the Invention
[0009] The purpose of this invention is to solve the problems existing in the prior art and to provide a silica aerogel particle / polyester fiber composite flocculant and its preparation method.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing silica aerogel particles / polyester fiber composite flocs involves first applying a first organic solvent to the surface of the polyester fiber flocs, and then applying a silica aerogel particle dispersion before the first organic solvent evaporates. After drying, the silica aerogel particles / polyester fiber composite flocs are obtained.
[0012] The dispersion medium in the silica aerogel particle dispersion is a second organic solvent;
[0013] The first organic solvent is an organic solvent that can activate the surface of the polyester fiber without damaging the main structure of the fiber; the second organic solvent is a volatile organic solvent that does not dissolve the main structure of the polyester fiber; the volatility of the first organic solvent is lower than that of the second organic solvent.
[0014] This invention, based on the principle of synergistic regulation of solvent activation and particle dispersion, achieves uniform distribution and stable anchoring of silica aerogel particles on the surface of a single polyester fiber. A first organic solvent capable of moderately interacting with the polyester molecular chains is used to activate the polyester fiber surface, improving the mobility of the surface chain segments and regulating the interfacial state. When the silica aerogel particle dispersion is applied to the activated polyester fiber surface, the first organic solvent remains on the surface, improving the wetting and spreading state of the silica aerogel particle dispersion. This allows the silica aerogel particle dispersion to distribute along the polyester fiber surface, reducing droplet shrinkage and localized enrichment of silica aerogel particles. During the subsequent drying process, a second organic solvent evaporates preferentially over the first, causing silica aerogel particles to deposit on the still-activated polyester fiber surface. As the first organic solvent further evaporates, local structural rearrangement on the polyester fiber surface generates numerous interfacial defects, forming a physical confinement for the silica aerogel particles, thereby reducing secondary migration and aggregation of the silica aerogel particles during the drying process. Therefore, silica aerogel particles are mainly loaded onto the surface of a single polyester fiber in a discrete state, while maintaining the original micron-level interconnected pores of the polyester fiber flocs, thus achieving uniform loading, stable anchoring, and synergistic effects of thermal insulation and air permeability.
[0015] As a preferred technical solution:
[0016] The method for preparing silica aerogel particles / polyester fiber composite flocs as described above, wherein the polyester fiber is one or more of polyethylene terephthalate (PET) fiber, polypropylene terephthalate (PTT) fiber, polybutylene terephthalate (PBT) fiber, polybutylene succinate (PBS) fiber, and polylactic acid (PLA) fiber.
[0017] In the preparation method of the silica aerogel particles / polyester fiber composite flocs described above, the first organic solvent is one or more of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0018] In the preparation method of the silica aerogel particles / polyester fiber composite flocs as described above, the second organic solvent is one or more of n-hexane, n-heptane, and cyclohexane.
[0019] The method for preparing silica aerogel particles / polyester fiber composite flocs as described above, wherein the basis weight of the polyester fiber flocs is 20~200 g / m³. 2 The surface of the polyester fiber wadding is the upper surface and / or the lower surface.
[0020] The method for preparing silica aerogel particles / polyester fiber composite flocs as described above, wherein the silica aerogel particles are hydrophobic silica aerogel particles with a diameter of 1~100μm and a specific surface area of 500~1000m² 2 / g, pore size is 10~50nm, porosity is greater than 90%.
[0021] In the above-described method for preparing silica aerogel particles / polyester fiber composite flocs, the concentration of the silica aerogel particle dispersion is 10~50 mg / mL.
[0022] In the method for preparing silica aerogel particles / polyester fiber composite flocs as described above, both the first organic solvent and the silica aerogel particle dispersion are applied by spraying; the amount of the first organic solvent sprayed onto the surface of the polyester fiber flocs is 0.02~0.10 L / m. 2 The spraying amount of silica aerogel particle dispersion on the surface of the polyester fiber wadding is 0.05~1.5L / m. 2 .
[0023] This invention also provides a silica aerogel particle / polyester fiber composite wadding, which is prepared by the method described above. The air permeability of the silica aerogel particle / polyester fiber composite wadding is more than 95% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particle / polyester fiber composite wadding is less than 95% of that of the polyester fiber wadding. After 100 cycles of compression, the retention rate of silica aerogel particles is high, indicating that the silica aerogel particles can be stably bonded to the surface of the polyester fiber.
[0024] Beneficial effects:
[0025] (1) The present invention uses organic solvent to activate polyester fiber flocs, thereby controlling the surface interface state of polyester fibers so that silica aerogel particles are uniformly attached to the surface of individual polyester fibers in a discrete state.
[0026] (2) The present invention retains the original micron-level interconnected pores of the polyester fiber floppy. Compared with the untreated polyester fiber floppy, the air permeability retention rate of the obtained silica aerogel particles / polyester fiber composite floppy is 95% or higher.
[0027] (3) The present invention enhances the physical bond between silica aerogel particles and polyester fiber surface through interface regulation, without the need for additional binders to fix the aerogel particles, which is beneficial to maintaining the lightweight and soft properties of the composite flocs.
[0028] (4) The silica aerogel particles / polyester fiber composite flocs of the present invention have extremely high aerogel loading uniformity, excellent air permeability and heat insulation performance. Attached Figure Description
[0029] Figure 1 This is a schematic diagram illustrating the structure and heat-insulating mechanism of the silica aerogel particle / polyester fiber composite wadding of the present invention;
[0030] Figure 2 This is a visualization of the non-covalent interaction analysis between silica aerogel particles and DMF in Example 2 of the present invention;
[0031] Figure 3 The figure shows the differential thermal scanning curves of the PET-coated film and the DMF-PET-coated film of the present invention; in the figure, a is the cooling scanning curve and b is the second heating scanning curve.
[0032] Figure 4 The figures show an electron microscope (EM) image of the silica aerogel particle / PET fiber composite floc obtained in Example 3 of this invention and an elemental distribution diagram of a single PET fiber loaded with silica aerogel particles. In the figures, a is a scanning electron microscope (SEM) image of the silica aerogel particle / PET fiber composite floc, b is an EEM image of a single fiber in the composite floc, c is a carbon elemental analysis diagram of a single fiber in the composite floc, d is an oxygen elemental analysis diagram of a single fiber in the composite floc, and e is a silicon elemental analysis diagram of a single fiber in the composite floc.
[0033] Figure 5The images shown are electron microscope (EM) images of the silica aerogel particles / polyester fiber composite flocs prepared in Examples 1-4 of this invention. In the images, a is an EEM image of the silica aerogel particles / polyester fiber composite flocs in Example 1, b is an EEM image of the silica aerogel particles / polyester fiber composite flocs in Example 2, c is an EEM image of the silica aerogel particles / polyester fiber composite flocs in Example 3, and d is an EEM image of the silica aerogel particles / polyester fiber composite flocs in Example 4.
[0034] Figure 6 This is an electron microscope image of the silica aerogel particles / PET fiber composite flocs prepared in Comparative Example 1 of the present invention;
[0035] Figure 7 This is an electron microscope image of the silica aerogel particles / PET fiber composite flocs prepared in Comparative Example 2 of the present invention;
[0036] Figure 8 Electron micrograph of the DMAc-PET coated film prepared according to the present invention;
[0037] Figure 9 This is an electron microscope image of the silica aerogel particles / PET fiber composite flocs prepared in Comparative Example 3 of the present invention;
[0038] In the figure, 1-silica aerogel particles / polyester fiber composite flocs, 2-polyester fiber, 3-silica aerogel particles. Detailed Implementation
[0039] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0040] The manufacturers and brands mentioned in the following embodiments are merely examples. The core of this invention lies in the technical solution itself, and it is not intended to limit specific manufacturers or brands. Products from other manufacturers and brands that meet the technical requirements and performance indicators specified in this invention can also meet the application requirements of this invention and are all feasible choices.
[0041] The following are the sources of the substances used in each embodiment:
[0042] Hydrophobic silica aerogel particles: manufactured by Shenzhen Zhongning Technology Co., Ltd., brand name AG-D aerogel powder.
[0043] The test methods for the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0044] Thermal conductivity: The thermal conductivity of the sample was determined using a Hot Disk (TPS 2500S, Sweden) probe with polyimide insulated probe F 5465 (gray cable), with a test power of 5mW and a test time of 10s.
[0045] Air permeability: In accordance with the requirements of GB / T 24218.15-2018 "Textiles - Test Methods - Part 15: Determination of air permeability", the air permeability of the samples was tested using an automatic air permeability meter (YG461E-Ⅲ, China).
[0046] Example 1
[0047] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0048] (1) Preparation of raw materials;
[0049] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2 It has an air permeability of 4010 mm / s and a thermal conductivity of 34.11 mW / m. -1 K -1 The polyester fiber is PET fiber;
[0050] First organic solvent: DMF;
[0051] Second organic solvent: n-hexane;
[0052] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0053] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 25 mg / mL.
[0054] (3) The first organic solvent is applied to the upper surface of the polyester fiber wadding by spraying to activate it; wherein the amount of the first organic solvent sprayed is 0.02 L / m 2 ;
[0055] (4) Before the first organic solvent evaporates, the silica aerogel particle dispersion is applied to the upper surface of the polyester fiber floc by spraying. After drying at 80°C for 2 hours, a silica aerogel particle / polyester fiber composite floc is obtained (its electron micrograph is shown in Figure 1). Figure 5 (As shown in Figure a); where the spraying amount of the silica aerogel particle dispersion is 0.09 L / m. 2 .
[0056] The final structure and heat-insulating mechanism of the silica aerogel particles / polyester fiber composite sheet are as follows: Figure 1As shown in the figure, the interwoven polyester fibers 2 form a meandering heat conduction path, and the attachment of silica aerogel particles 3 forms a rich solid-gas interface, which significantly increases phonon scattering and reduces solid-state heat conduction. At the same time, the silica aerogel particles 3 attached to the surface of polyester fibers 2 reduce some pore space and weaken the gas conduction inside the silica aerogel particle / polyester fiber composite sheet 1, thereby improving the thermal insulation performance of the silica aerogel particle / polyester fiber composite sheet 1.
[0057] The air permeability of the silica aerogel particles / polyester fiber composite wadding is 95.8% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particles / polyester fiber composite wadding is 95% of that of the polyester fiber wadding.
[0058] To analyze the effect of DMF on the crystallization properties of polyester, PET-coated films and DMF-PET-coated films were prepared, as detailed below:
[0059] PET coated film: Polyester fiber flakes (one of the raw materials prepared in Example 1) were dissolved in hexafluoroisopropanol to prepare a uniform solution with a concentration of 20wt%; then the prepared solution was coated on a polytetrafluoroethylene calendered film using a coater with a gap of 100μm to form a wet film of a specified thickness, and then annealed at 100°C for 10min.
[0060] DMF-PET Coated Film: The same PET coated film was prepared using the method described above. DMF was applied to the upper surface of the PET coated film by spraying (the spraying amount of DMF was 0.02 L / m). 2 The DMF-PET coated film was obtained by solvent activation treatment and drying at 80℃ for 2 hours.
[0061] Simultaneously, a differential scanner was used to scan the PET-coated film and the DMF-PET-coated film to obtain the following results: Figure 3 The curves shown indicate that the cold crystallization behavior of the PET coated film changed after DMF treatment. This suggests that DMF can regulate the movement state of the chain segments on the surface of the PET coated film, forming an interface structure that is conducive to the adhesion of silica aerogel particles. This inhibits the aggregation of silica aerogel particles and the accumulation at the overlapping nodes, allowing the composite flocs to maintain a continuous pore structure.
[0062] Example 2
[0063] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0064] (1) Preparation of raw materials;
[0065] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2 It has an air permeability of 4010 mm / s and a thermal conductivity of 34.11 mW / m. -1 K -1 The polyester fiber is PET fiber;
[0066] First organic solvent: DMF;
[0067] Second organic solvent: n-hexane;
[0068] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0069] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 25 mg / mL.
[0070] (3) The first organic solvent is applied to the upper and lower surfaces of the polyester fiber wadding by spraying to activate it; wherein the total amount of the first organic solvent sprayed is 0.04 L / m 2 The amount of coating on the upper and lower surfaces is the same;
[0071] (4) Before the first organic solvent evaporates, the silica aerogel particle dispersion is applied to the upper and lower surfaces of the polyester fiber flocs by spraying. After drying at 80°C for 2 hours, a silica aerogel particle / polyester fiber composite flocs are obtained (the non-covalent interaction analysis of the silica aerogel particles and DMF is as follows). Figure 2 As shown, a strong van der Waals force exists between DMF and silica aerogel, which weakens the mutual attraction between silica aerogel particles and helps reduce the tendency for aerogel particles to aggregate. The total amount of silica aerogel particle dispersion sprayed is 0.18 L / m³. 2 The amount of coating applied to the upper and lower surfaces is the same.
[0072] The final silica aerogel particle / polyester fiber composite flocculent was prepared (its electron micrograph is shown in the figure). Figure 5 The air permeability of the silica aerogel particles / polyester fiber composite wadding is 95.24% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particles / polyester fiber composite wadding is 89% of that of the polyester fiber wadding.
[0073] Comparative Example 1
[0074] A method for preparing silica aerogel particles / polyester fiber composite flocs is basically the same as in Example 2, except that step (3) is omitted.
[0075] The electron micrograph of the final silica aerogel particle / polyester fiber composite flocs is shown below. Figure 6 As shown in the figure, a large number of fine particles are deposited on the surface of PET fibers, which are tightly packed and mixed with agglomerates, but the pores between fibers still exist.
[0076] The air permeability of the silica aerogel particles / polyester fiber composite wadding is 93.7% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particles / polyester fiber composite wadding is 97.5% of that of the polyester fiber wadding. Powder can be observed flying when the composite wadding is moved slightly.
[0077] A comparison of Comparative Example 1 and Example 2 reveals that the silica aerogel particles in the silica aerogel particle / polyester fiber composite sheet prepared in this comparative example are mainly deposited on the polyester fiber surface in the form of a fine powder coating layer and local agglomerates. This fails to fully utilize the thermal insulation effect of the aerogel particles. This is because hexane only acts as a dispersion and transport medium for the aerogel particles; its interaction with the surface molecular chains of the polyester fibers is weak, making it difficult to significantly improve the mobility of the polyester fiber surface chain segments. After the hexane evaporates, the aerogel particles can only be deposited on the unactivated fiber surface through weak physical contact. The silica aerogel particles are more prone to secondary migration and local agglomeration during subsequent drying and processing, leading to a decrease in the air permeability and an increase in the thermal conductivity of the composite sheet.
[0078] Comparative Example 2
[0079] A method for preparing silica aerogel particles / polyester fiber composite flocs is basically the same as in Example 2, except that the first organic solvent in steps (1) and (3) is replaced with an equal volume of ethanol.
[0080] The electron micrograph of the final silica aerogel particle / polyester fiber composite flocs is shown below. Figure 7 As shown in the figure, the particle coverage varies greatly between different fibers or different locations of the same fiber, with localized aggregation and nodal enrichment.
[0081] The air permeability of the silica aerogel particles / polyester fiber composite wadding is 93.3% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particles / polyester fiber composite wadding is 98.4% of that of the polyester fiber wadding. Powder can be observed flying when the composite wadding is moved slightly.
[0082] Comparing Comparative Example 2 and Example 2, it can be seen that the air permeability of the silica aerogel particle / polyester fiber composite flocculant prepared in this comparative example decreases while the thermal conductivity increases. The silica aerogel particles are locally enriched at the fiber edges and fiber overlaps. This is because although ethanol can improve the wetting of the fiber surface by the dispersion, under the conditions of this process, ethanol has virtually no effect on the surface of the polyester fiber, exhibiting the same morphology and crystallinity as the untreated polyester fiber. Therefore, the silica aerogel particles cannot be stably and uniformly distributed on the surface of each fiber, and the local accumulation at the overlap nodes narrows some pores, making it difficult to simultaneously obtain both low thermal conductivity and high air permeability.
[0083] Comparative Example 3
[0084] A method for preparing silica aerogel particles / polyester fiber composite flocs is basically the same as in Example 2, except that the first organic solvent in steps (1) and (3) is replaced with an equal volume of N,N-dimethylacetamide (DMAc).
[0085] The electron micrograph of the final silica aerogel particle / polyester fiber composite flocs is shown below. Figure 9 As shown in the figure, after treating the polyester fiber flocs with DMAc as the first organic solvent, a continuous and relatively thick rough coating layer is formed on the surface of the polyester fibers. Particles are obviously accumulated at the fiber overlap points, and sheet-like or bridging connections appear in some areas. The pore size between PET fibers is significantly reduced.
[0086] The air permeability of the silica aerogel particles / polyester fiber composite wadding is 83.6% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particles / polyester fiber composite wadding is 102% of that of the polyester fiber wadding.
[0087] Comparing Comparative Example 3 and Example 2, it can be seen that the air permeability of the silica aerogel particle / polyester fiber composite flocculant prepared in this comparative example decreases, while the thermal conductivity increases. Figure 9As shown in the microstructure, silica aerogel particles form a thick and continuous coating layer on the surface of polyester fibers. Particle accumulation and bridging occur between some adjacent fibers, obstructing the original interconnected pores between fibers. This is because DMAc produces an uneven solvation effect on the polyester fiber surface, leading to localized swelling and slight surface erosion in some areas, thus reducing the uniformity of the interface state and morphology of the fiber surface. This uneven interface state further increases the tendency for local deposition and aggregation of silica aerogel particles, causing them to accumulate at fiber overlap nodes and form a relatively continuous coating layer and cross-fiber bridging structures. These structures increase the resistance to airflow through the fusible fibers, resulting in decreased air permeability. Simultaneously, the local accumulation of silica aerogel particles reduces the uniformity of their distribution within the fiber network and increases the contact between silica aerogel particles and between silica aerogel particles and fibers. Under similar aerogel addition levels, the effect on regulating the gas-phase and solid-phase heat transfer paths is weaker than in Example 2, therefore its thermal conductivity is relatively higher.
[0088] To analyze the effect of DMAc on the crystallization properties of polyester, a DMAc-PET coated film was prepared, as follows:
[0089] First, polyester fiber flakes (one of the raw materials prepared in Example 2) were dissolved in hexafluoroisopropanol to prepare a uniform solution with a concentration of 20wt%; then, the prepared solution was coated onto a polytetrafluoroethylene calendered film using a coater with a gap of 100μm to form a wet film of a specified thickness, and then annealed at 100°C for 10min.
[0090] Then, DMAc was applied to the upper surface of the PET coated film by spraying (DMF spraying amount was 0.02 L / m). 2 Solvent activation treatment was performed on the DMAc-PET coated film, and then dried at 80℃ for 2 hours to obtain the DMAc-PET coated film.
[0091] Electron micrograph of the DMAc-PET coated film is shown below. Figure 8 As shown in the figure, after treating polyester fiber flakes with DMAc, DMAc disrupts the surface morphology of the PET film, and the smooth PET film becomes rough after DMAc treatment.
[0092] Example 3
[0093] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0094] (1) Preparation of raw materials;
[0095] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2It has an air permeability of 4010 mm / s and a thermal conductivity of 34.11 mW / m. -1 K -1 The polyester fiber is PET fiber;
[0096] First organic solvent: DMF;
[0097] Second organic solvent: n-hexane;
[0098] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0099] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 25 mg / mL.
[0100] (3) The first organic solvent is applied to the upper and lower surfaces of the polyester fiber wadding by spraying to activate it; wherein the total amount of the first organic solvent sprayed is 0.06 L / m 2 The amount of coating on the upper and lower surfaces is the same;
[0101] (4) Before the first organic solvent evaporates, the silica aerogel particle dispersion is applied to the upper and lower surfaces of the polyester fiber flocs by spraying. After drying at 80°C for 2 hours, a silica aerogel particle / polyester fiber composite flocs are obtained (its electron micrograph and the elemental distribution of a single PET fiber loaded with silica aerogel particles are shown in the figure). Figure 4 As shown in the figure, silica aerogel particles are uniformly attached to the surface of a single PET fiber in a discrete state; the total amount of silica aerogel particle dispersion sprayed is 0.27 L / m. 2 The amount of coating applied to the upper and lower surfaces is the same.
[0102] The final silica aerogel particle / polyester fiber composite flocculent was prepared (its electron micrograph is shown in the figure). Figure 5 As shown in Figure c), the air permeability of the composite wadding (silica aerogel particles / polyester fiber) is 95% of that of the polyester fiber wadding. The thermal conductivity of the composite wadding is 81% of that of the polyester fiber wadding. After 100 cycles of compression (compression deformation of 60%), the thermal conductivity of the composite wadding is 103.3% of that before the 100 cycles of compression. The change in thermal conductivity of the composite wadding before and after cyclic compression is not significant. Therefore, it can be concluded that silica aerogel particles can be stably bonded to the surface of polyester fibers.
[0103] Example 4
[0104] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0105] (1) Preparation of raw materials;
[0106] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2 It has an air permeability of 4010 mm / s and a thermal conductivity of 34.11 mW / m. -1 K -1 The polyester fiber is PET fiber;
[0107] First organic solvent: DMF;
[0108] Second organic solvent: n-hexane;
[0109] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0110] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 25 mg / mL.
[0111] (3) The first organic solvent is applied to the upper and lower surfaces of the polyester fiber wadding by spraying to activate it; wherein the total amount of the first organic solvent sprayed is 0.08 L / m 2 The amount of coating on the upper and lower surfaces is the same;
[0112] (4) Before the first organic solvent evaporates, a silica aerogel particle dispersion is applied to the upper and lower surfaces of the polyester fiber flocs by spraying. After drying at 80°C for 2 hours, a silica aerogel particle / polyester fiber composite flocs are obtained; wherein, the total amount of silica aerogel particle dispersion sprayed is 0.36 L / m 2 The amount of coating applied to the upper and lower surfaces is the same.
[0113] The final silica aerogel particle / polyester fiber composite flocculent was prepared (its electron micrograph is shown in the figure). Figure 5 The air permeability of the silica aerogel particles / polyester fiber composite wadding (as shown in d) is 95.2% of that of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particles / polyester fiber composite wadding is 84% of that of the polyester fiber wadding.
[0114] Example 5
[0115] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0116] (1) Preparation of raw materials;
[0117] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2It has an air permeability of 3890 mm / s and a thermal conductivity of 34.53 mW / m. -1 K -1 The polyester fiber is PET fiber;
[0118] First organic solvent: DMF;
[0119] Second organic solvent: cyclohexane;
[0120] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0121] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 20 mg / mL.
[0122] (3) The first organic solvent is applied to the upper surface of the polyester fiber wadding by spraying to activate it; wherein the amount of the first organic solvent sprayed is 0.02 L / m 2 ;
[0123] (4) Before the first organic solvent evaporates, a silica aerogel particle dispersion is applied to the upper surface of the polyester fiber floc by spraying. After drying at 80°C for 2 hours, a silica aerogel particle / polyester fiber composite floc is obtained; wherein, the spraying amount of silica aerogel particle dispersion is 0.09 L / m 2 .
[0124] The final silica aerogel particle / polyester fiber composite wadding has an air permeability of 96.2% of that of the polyester fiber wadding, and a thermal conductivity of 94% of that of the polyester fiber wadding.
[0125] Example 6
[0126] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0127] (1) Preparation of raw materials;
[0128] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2 It has an air permeability of 3890 mm / s and a thermal conductivity of 34.53 mW / m. -1 K -1 The polyester fiber is PET fiber;
[0129] First organic solvent: DMSO;
[0130] Second organic solvent: n-heptane;
[0131] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0132] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 30 mg / mL.
[0133] (3) The first organic solvent is applied to the upper surface of the polyester fiber wadding by spraying to activate it; wherein the amount of the first organic solvent sprayed is 0.02 L / m 2 ;
[0134] (4) Before the first organic solvent evaporates, a silica aerogel particle dispersion is applied to the upper surface of the polyester fiber flocculent by spraying. After drying at 100°C for 2 hours, a silica aerogel particle / polyester fiber composite flocculent is obtained; wherein, the spraying amount of the silica aerogel particle dispersion is 0.09 L / m 2 .
[0135] The final silica aerogel particle / polyester fiber composite wadding has an air permeability of 95.6% of that of the polyester fiber wadding, and a thermal conductivity of 92% of that of the polyester fiber wadding.
[0136] Example 7
[0137] A method for preparing silica aerogel particles / polyester fiber composite flocculants, comprising the following steps:
[0138] (1) Preparation of raw materials;
[0139] Polyester fiber wadding: 40cm (length) × 40cm (width), weight 45g / m² 2 It has an air permeability of 3890 mm / s and a thermal conductivity of 34.53 mW / m. -1 K -1 The polyester fiber is PLA fiber;
[0140] First organic solvent: DMF;
[0141] Second organic solvent: n-hexane;
[0142] Silica aerogel particles: Hydrophobic silica aerogel particles;
[0143] (2) The silica aerogel particles were uniformly dispersed in a second organic solvent to obtain a silica aerogel particle dispersion with a concentration of 15 mg / mL.
[0144] (3) The first organic solvent is applied to the upper surface of the polyester fiber wadding by spraying to activate it; wherein the amount of the first organic solvent sprayed is 0.02 L / m 2 ;
[0145] (4) Before the first organic solvent evaporates, a silica aerogel particle dispersion is applied to the upper surface of the polyester fiber floc by spraying. After drying at 80°C for 2 hours, a silica aerogel particle / polyester fiber composite floc is obtained; wherein, the spraying amount of silica aerogel particle dispersion is 0.09 L / m 2 .
[0146] The final silica aerogel particle / polyester fiber composite wadding has an air permeability of 96.6% of that of the polyester fiber wadding, and a thermal conductivity of 95% of that of the polyester fiber wadding.
[0147] Example 8
[0148] A method for preparing silica aerogel particles / polyester fiber composite flocs is basically the same as in Example 7, except that the polyester fiber flocs used have an air permeability of 3956 mm / s and a thermal conductivity of 34.72 mW / m. -1 K -1 The polyester fiber is PTT fiber.
[0149] The final silica aerogel particle / polyester fiber composite wadding has an air permeability of 97.2% of that of the polyester fiber wadding, and a thermal conductivity of 95% of that of the polyester fiber wadding.
[0150] Example 9
[0151] A method for preparing silica aerogel particles / polyester fiber composite flocs is basically the same as in Example 7, except that the polyester fiber flocs used have an air permeability of 3726 mm / s and a thermal conductivity of 34.58 mW / m. -1 K -1 The polyester fiber is PBT fiber.
[0152] The final silica aerogel particle / polyester fiber composite wadding has an air permeability of 96.7% of that of the polyester fiber wadding, and a thermal conductivity of 94.9% of that of the polyester fiber wadding.
[0153] Example 10
[0154] A method for preparing silica aerogel particles / polyester fiber composite flocs is basically the same as in Example 7, except that the polyester fiber flocs used have an air permeability of 3907 mm / s and a thermal conductivity of 35.03 mW / m. -1 K -1 The polyester fiber is a PBS fiber.
[0155] The final silica aerogel particle / polyester fiber composite wadding has an air permeability of 96.3% of that of the polyester fiber wadding, and a thermal conductivity of 93.7% of that of the polyester fiber wadding.
[0156] Unless otherwise specified, all of the above embodiments and comparative examples are considered to be carried out at room temperature.
[0157] In the above embodiments and comparative examples, after the first organic solvent is applied to the surface of the polyester fiber floppy by spraying, there is no need to let it stand, and the process proceeds directly to the next step, in which the silica aerogel particle dispersion is applied to the surface of the polyester fiber floppy by spraying.
Claims
1. A method for preparing silica aerogel particles / polyester fiber composite flocs, characterized in that, First, a first organic solvent is applied to the surface of the polyester fiber wadding. Then, before the first organic solvent evaporates, a silica aerogel particle dispersion is applied. After drying, a silica aerogel particle / polyester fiber composite wadding is obtained. The dispersion medium in the silica aerogel particle dispersion is a second organic solvent; The first organic solvent is an organic solvent that can activate the surface of the polyester fiber without damaging the main structure of the fiber; the second organic solvent is a volatile organic solvent that does not dissolve the main structure of the polyester fiber; the volatility of the first organic solvent is lower than that of the second organic solvent.
2. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 1, characterized in that, Polyester fiber is one or more of polyethylene terephthalate fiber, propylene terephthalate fiber, polybutylene terephthalate fiber, polybutylene succinate fiber, and polylactic acid fiber.
3. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 2, characterized in that, The first organic solvent is one or more of N,N-dimethylformamide and dimethyl sulfoxide.
4. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 3, characterized in that, The second organic solvent is one or more of n-hexane, n-heptane, and cyclohexane.
5. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 1, characterized in that, The basis weight of polyester fiber wadding is 20~200g / m². 2 The surface of the polyester fiber wadding is the upper surface and / or the lower surface.
6. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 1, characterized in that, The silica aerogel particles are hydrophobic silica aerogel particles with a diameter of 1~100μm and a specific surface area of 500~1000m². 2 / g, pore size is 10~50nm, porosity is greater than 90%.
7. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 1, characterized in that, The concentration of the silica aerogel particle dispersion is 10~50 mg / mL.
8. The method for preparing a silica aerogel particle / polyester fiber composite sheet according to claim 7, characterized in that, Both the first organic solvent and the silica aerogel particle dispersion were applied by spraying; the amount of the first organic solvent sprayed onto the surface of the polyester fiber wadding was 0.02~0.10 L / m. 2 The spraying amount of silica aerogel particle dispersion on the surface of the polyester fiber wadding is 0.05~1.5L / m. 2 .
9. A silica aerogel particle / polyester fiber composite sheet, characterized in that, The silica aerogel particle / polyester fiber composite wadding is prepared by the preparation method of any one of claims 1 to 8; the air permeability of the silica aerogel particle / polyester fiber composite wadding is more than 95% of the air permeability of the polyester fiber wadding, and the thermal conductivity of the silica aerogel particle / polyester fiber composite wadding is less than 95% of the thermal conductivity of the polyester fiber wadding.
Citation Information
Patent Citations
Method for manufacturing low-dust high-insulation aerogel blanket
EP3281928B1
Low-dust silica aerogel blanket and method for manufacturing same
EP3712111A1
Aerogel blanket and method of production
US9399864B2